Green space system planning and optimization coupling landscape pattern analysis with spatial models: a case study of Fuzhou, China - Chen, Jingru; Zhou, Qingqing; Wu, Shengzhen; Huang, Yabing (Frontiers in Environmental Science, 2025)
The network structure and connectivity of green spaces play a crucial role in ecosystem functionality. However, there are still many challenges in improving the structure of urban green space systems (GSS) through quantitative scientific methods. In particular, there is an obvious lack of how to integrate quantitative landscape pattern analysis with multi-scenario network analysis, which leads to insufficient scientific and operationalization of green space system optimization. This paper aims to present a methodological framework for planning and constructing green networks within urban green space system planning (GSSP), using the GSSP of Fuzhou as a case study. The results of the study show that: (1) 18 GPAs were classified with GPA 4 (2287.66 km2) showing the highest connectivity importance (dPC = 88.459); (2) the Min River corridor (GPA 10) and urban coastal wetlands (GPA 17) emerged as strategically vital despite spatial constraints; (3) scenario analysis identified Scenario 1 (α = 0.26, CR = 0.999) as the optimal network configuration. This research establishes a structured GSSP approach that not only addresses urban ecological continuity issues but also provides a replicable model for enhancing biodiversity and ecological health in urban settings, offering insights and implications for achieving sustainable development goals in future regions.